121k views
1 vote
What is the inverse of h(x)=3 square root x -3

User Katerlouis
by
5.7k points

1 Answer

2 votes

Answer:

y =
(x^(2) + 27)/(8)

Explanation:

To find the inverse, we will set it equal to y, switch the x and y values, then solve for y.

[Given] h(x)=3 square root x -3

[Rewrite] y = 3
√(x-3)

[Switch values] x = 3
√(y-3)

[Square both sides] x² = 9(y - 3)

[Distrubte] x² = 8y - 27

[Add 27 to both sides & flip equation] 8y = x² + 27

[Divide both sides of 8] y =
(x^(2) + 27)/(8)

Have a nice day!

I hope this is what you are looking for, but if not - comment! I will edit and update my answer accordingly. (ノ^∇^)

- Heather

User BeetDemGuise
by
5.2k points